Rational synthesis of novel biocompatible thermoresponsive block copolymer worm gels. Issue 22 (17th May 2021) - Beattie, Deborah L.; Mykhaylyk, Oleksandr O.; Ryan, Anthony J.; Armes, Steven P.
Abstract : Judicious control over the mean degree of polymerization of each block in a amphiphilic diblock copolymer ensures that the corresponding worm gel exhibits thermoreversible (de)gelation behavior, as judged by TEM, SAXS and rheology studies. Abstract : It is well known that reversible addition–fragmentation chain transfer (RAFT) aqueous dispersion polymerization of 2-hydroxypropyl methacrylate (HPMA) enables the rational design of diblock copolymer worm gels. Moreover, such hydrogels can undergo degelation on cooling below ambient temperature as a result of a worm-to-sphere transition. However, only a subset of such block copolymer worms exhibit thermoresponsive behavior. For example, PMPC26 –PHPMA280 worm gels prepared using a poly(2-(methacryloyloxy)ethyl phosphorylcholine) (PMPC26 ) precursor do not undergo degelation on cooling to 6 °C (see S. Sugihara et al., J. Am. Chem. Soc., 2011, 133, 15707–15713). Informed by our recent studies (N. J. Warren et al., Macromolecules, 2018, 51, 8357–8371), we decided to reduce the mean degrees of polymerization of both the PMPC steric stabilizer block and the structure-directing PHPMA block when targeting a pure worm morphology. This rational approach reduces the hydrophobic character of the PHPMA block and hence introduces the desired thermoresponsive character, as evidenced by the worm-to-sphere transition (and concomitant degelation) that occurs on cooling a PMPC15 –PHPMA150 worm gel from 40 °C to 6 °C. Moreover, worms are reconstituted on returning to 40 °C and the original gel modulus is restored. This augurs well for potential biomedical applications, which will be examined in due course. Finally, small-angle X-ray scattering studies indicated a scaling law exponent of 0.67 (≈2/3) for the relationship between the worm core cross-sectional diameter and the PHPMA DP for a series of PHPMA-based worms prepared using a range of steric stabilizer blocks, which is consistent with the strong segregation regime for such systems.